Perbandingankenaikan berat badan bblr yang Diberi asi dan susu formula pada dua minggu Pertama perawatan - Rosdiana - Susanti; Oswati - Hasanah; Gamya Tri Utami (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2014)
This research goal was to compare the weight increase of low birth weight (LBW) neonates that was given breast feeding and formula feeding in Perinatology unit at Arifin Achmad Hospital Pekanbaru. This was descriptive comparative research with retrospective approach.  The total number of respondent was 279 taken from medical record in 2010-2012. The instruments in this research was entry sheet that was consist of information about nutrition  and weight increase recorded during first-two weeks of treatment. The data were analyzed by univariate and bivariate with Wilcoxon and Mann Whitney test. Wilcoxon test showed there was weight gain in each group of feeding (P value: 0,000), further more Mann-whitney test showed a significant differences weight gain between breast feeding and formula feeding groups with P value (0,007) < α (0,05).  This result recommended breast feeding as nursing intervention for LBW neonates in perinatology unit. Keywords: breast milk, weight, low birth weight, formula References: 27 (2006-2013)